An analysis on the use of cohesive devices in improving students' ability in writing recount text at the ninth grade of SMP Negeri 1 Siantar - Tiodor Sihotang; Herman Herman; Yanti Kristina Sinaga (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze the use of cohesive devices in improving students’ ability to write recount texts at the ninth grade of SMP Negeri 1 Siantar. A qualitative research design was employed, with data collected from 30 students’ written texts based on their personal experiences. The analysis was guided by Halliday and Hasan’s cohesion framework, which includes grammatical cohesion (reference, substitution, ellipsis, and conjunction) and lexical cohesion. The findings revealed a total of 1,025 cohesive devices, with reference (38.82%) and conjunction (34.14%) as the most dominant types, followed by lexical cohesion (26.04%). In contrast, substitution (0.68%) and ellipsis (0.29%) were rarely used. These results indicate that students possess a basic understanding of cohesion, particularly in organizing ideas and maintaining textual flow. However, their use of cohesive devices remains limited in variation and sophistication. Therefore, more explicit instruction and practice are recommended to enhance students’ mastery of diverse cohesive strategies and improve overall writing quality.